2018
DOI: 10.1111/1755-5922.12466
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of tolvaptan on atrial remodeling induced by chronic intermittent hypoxia in rats

Abstract: CIH-induced significant atrial remodeling in our rat model, which was attenuated by tolvaptan. These changes may be explained due to alterations in miR-21/Spry1/ERK/MMP-9, miR-21/PTEN/PI3K/AKT, and NF-κB pathways by tolvaptan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“… 19 Goudis and Ketikoglou 20 described that obstructive sleep apnea was associated with AF, which may implicate the pathophysiological mechanisms of AF. In addition, Zhang et al 21 showed that the percentage of the atrial collagen fraction in the CIH group was significantly increased compared with the values recorded in the control and intervention groups. Therefor, we created an atrial fibrosis model by CIH for further experimentation in this study.…”
Section: Discussionmentioning
confidence: 93%
“… 19 Goudis and Ketikoglou 20 described that obstructive sleep apnea was associated with AF, which may implicate the pathophysiological mechanisms of AF. In addition, Zhang et al 21 showed that the percentage of the atrial collagen fraction in the CIH group was significantly increased compared with the values recorded in the control and intervention groups. Therefor, we created an atrial fibrosis model by CIH for further experimentation in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Total protein was extracted by RIPA lysis buffer (KeyGEN Biotech, Nanjing) and then underwent Western blot analysis, as described elsewhere [18]. b-actin served as the loading control.…”
Section: Western Blottingmentioning
confidence: 99%
“…We then examined the effects of BO treatment on the level of Akt phosphorylation at serine 473 (Fig. 4 G), since decreased Akt phosphorylation is involved in the pathogenesis of atrial remodeling and oxidative stress in the atrium, leading to AF 41 , 42 . Akt phosphorylation (Ser-473) was significantly decreased in the atrium of the BO group (Control ( n = 6) vs. BO (n = 7): 1.0 ± 0.1 vs. 0.7 ± 0.1 A.U., P < 0.01 vs. Control).…”
Section: Resultsmentioning
confidence: 99%
“…We then examined the effects of BO treatment on the level of Akt phosphorylation at serine 473 ( Fig. 4G), since decreased Akt phosphorylation is involved in the pathogenesis of atrial remodeling and oxidative stress in the atrium, leading to AF 41,42 . Akt phosphorylation (Ser-473) Supplementary Fig.…”
Section: Effects Of Bo On Akt Phosphorylationmentioning
confidence: 99%